PENGEMBANGAN MODUL AUDIO VISUAL UNTUK PELATIHAN PEMBIAKAN TANAMAN SECARA VEGETATIF - -, Rahmah -; Asyhar, Rayandra -; Rusdi, Muhammad - (Program Magister Teknologi Pendidikan Universitas Jambi, 2011)
This article is based on the developmental research which is aimed at producing an audio visual module applied in vegetative plants cultivation training. A model development is adapted from Dick and Carey design (2005). The present model has been validated by some experts such as media expert and teaching-learning expert. It also has been tested to the students of the eleventh grade at the SMK 2 Muaro Jambi. The results revealed that the product (the audio visual module) is quite applicable to improve students’ knowledge and skills in plants’ production. Keywords: audio-visual modules, vegetative plant cultivation